Обґрунтування вибору класу точності для навігаційної гіс прецизійного землеробства - Сініцин, О. В. (Energy and Automation, 2017)
JUSTIFICATION OF THE CHOICE CLASS OF ACCURACY FOR NAVIGATION, GIS, PRECISION AGRICULTUREA. SinitsynAbstract. The concept of technologies of precision agriculture are described and its key element – navigation geographic information system. The classification accuracy of determining the location of units and calculated and the choice of optimal accuracy class for process operations performed using the technology of parallel driving.Keywords: precision agriculture, precision location, parallel navigation, GIS.Precision (precise point) agriculture (PZ) is an innovative new way of farming that can improve crop yields while maintaining soil fertility, saving of material and financial resources and reduction of anthropogenic pressure on the environment [1].ON aimed at improving productivity, reducing production costs, reducing transaction costs and saving the environment. The use of technology, provides 30% increase in yield, savings in fertilizer, herbicides and the like. In the basis of scientific concepts of precision agriculture are unaware of the existence of heterogeneity within a single field. For the evaluation and detection of these inhomogeneities we use the latest technologies, such as global positioning system GPS, sensors, aerial and satellite imagery, as well as special programs for agromanagement on the basis of geographic information systems (GIS) [2].A key element of the technology of using a navigation system, which can reduce operating costs such as labor costs, fertilizer costs, and fuel. The aim of the research is to justify the choice of method determine the precise location of units and to construct a mathematical model of the relation between the accuracy of the positioning units and the number of technological operations using the technology of parallel driving.The materials and methods. To implement navigation in GIS is necessary to solve complex tasks (tillage, irrigation, spraying, etc.) at different stages of the life cycle of crops. The implementation of these tasks determines the choice of method and accuracy of determining the location of the units.In the article the attention is focused on the technological aspects of parallel driving units, which is impossible without accurate location in real time. The results of the research. The use of the system became possible due to the availability of technical means of positioning units (tractors, combine harvesters, tractor tools using satellite navigation systems, the use of such systems allowed to obtain agriculture data about the accurate location about typical for this area of the field specific parameters: the provision of nutrients, humidity, the condition of the plants. To position objects in the currently operating global satellite navigation systems GPS (USA), GLONASS (Russia), Galileo (European Union). Each system consists of 24 satellites orbiting the Earth in circular orbits at an altitude of about 19 to 23 thousand km, with a frequency of 2 times per day, transmitting navigation signals.Conclusions. It can be concluded that the correlation coefficient significant (meaningful), and the relationship between the dependent variable and the independent factors are significant.In the article the classification accuracy of the positioning units and the calculated and the choice of optimal accuracy class for process operations performed using the technology of parallel driving.Based on the foregoing and navigation GIS 4 class of accuracy of the positioning of the object is the most effective instrument for the implementation of technology.